Strategies For Increasing Compliance With Fall Risk Prevention In Outstanding Physiotherapy Services In Installation Of Medical Rehabilitation In Pertamina Central Hospital - Yuli Arnita Pakpahan; Agusta Dian; Sudarto; Sunarto; Parmo; Rizki; Nadia Putri Utami (Universitas Binawan, 2022)
Fall prevention is one component of the 6 patient safety goals. The implementation of fall prevention is one of the components of patient safety that must be carried out in order to maintain the quality of service at Pertamina Central Hospital Jakarta. Physiotherapy has a role in assessing the risk of falling and conducting interventions and implementation according to the fall risk category. The purpose of community service is to analyze what factors affect the quality of outpatient physiotherapy services at the RSPP medical rehabilitation installation and look for strategies to improve the quality of physiotherapy services. Activities are carried out through in-depth interviews and direct observation, then perform a fishbone analysis to determine the factors causing the problem, determine problem solving priorities with USG analysis (urgency, seriousness, growth) followed by strategy formulation with SWOT analysis (strength, Weakness, Opportunity, Threats) . The strategy applied to this community service activity is educating families and patients about the risk of falling and to physiotherapy by filling out a fall risk form and also for management suggesting the holding of special toilets or barrier-free showers and handling in the toilet and around the outpatient room.